Exploring the cultivation effects of anime consumption in developing parasocial relationships among Malaysian university students - Pua, Wei Yi (2023)
There is a gap in existing research on the cultivation effects of long-term exposure to media content in the development of parasocial relationships. With anime’s increasing popularity, the purpose of this paper is to explore the cultivation effects of anime consumption in developing parasocial relationships among Malaysian university students aged between 18 and 25. This study aims to (i) determine the impact of heavy anime consumption in developing parasocial relationships, and (ii) investigate the difference in impact between male and female Malaysian university students. A combination of sampling methods including convenience sampling, snowball sampling, and voluntary response sampling were used to distribute a web-based, selfadministered survey questionnaire consisting of 36 close-ended questions to 310 Malaysian university students. The findings revealed that there is a relationship between heavy viewing and the development of parasocial relationships, and that the impact was more prevalent among female than male students. These findings will contribute to the existing gap in research between Cultivation theory and parasocial relationship. The present study is limited by its use of crosssectional data. Therefore, it is suggested that future studies utilise longitudinal designs to investigate the long-term impacts of anime consumption on the development of parasocial relationships.